Edible crickets as a possible way to curb protein-energy malnutrition: Nutritional status, food applications, and safety concerns - Syed Ali Hassan; Ammar B. Altemimi; Adeel Asim Hashmi; Sandal Shahzadi; Waqar Mujahid; Ahsan Ali; Zuhaib F. Bhat; Saima Naz; Ahmad Nawaz; Gholamreza Abdi; Rana Muhammad Aadil (Food Chemistry: X, 2024)
Protein malnutrition is a major public health concern in the developing world. The livestock products are a good source of high-quality protein, but the livestock industry is a source of pollution and one of the leading causes of climate change because the slaughtering of animals results in the accumulation of waste, offals, and several inedible body portions. The rapid increase in the human population and inadequate supply of traditional protein sources have driven a search for novel and alternative protein sources such as edible insects. This review extensively explores the nutritional value, allergenicity, and safety considerations associated with consuming common house crickets and other related insect species. A wide range of cricket protein-based products are currently available and provide some attractive options to the consumers such as protein-enriched bakery products and gluten-free bread for celiac patients. The cricket protein hydrolysates are used as preservatives to improve the stability of cheddar cheese and goat meat emulsions during storage. The risks associated with edible crickets and their products are bacteria, mycotoxins, polychlorinated dibenzodioxins, pesticide residues, heavy metals, and the presence of allergenic proteins.